Aviation's Impact on Agriculture and Its Animal Habitat - Diederiks-Verschoor, IH. PH. (Universiti Putra Malaysia Press, 1997)
Aviation also plays a role in agriculture, where aircraft are used for cropdusting. The benefits of cropdusting are evident but this is also an activity, which may lead to damage to the environment. The article discusses some of these aspects, viewed in the light of the Rome Convention of 1952 on damage caused to third parties on the surface. Also the applicability of national laws and case law is considered, together with the responsibility for the damage caused by spraying. As this kind of aircraft has to fly at low altitude, the noise may also affect animals.